2020
DOI: 10.1111/rda.13832
|View full text |Cite
|
Sign up to set email alerts
|

UFMylation is associated with LPS‐induced inflammatory response in goat endometrial epithelial cells

Abstract: The endometrium plays an important role in the defence against invading pathogens, although the mechanisms are not clear. UFMylation is a recently discovered novel ubiquitination-like modification system that plays a pivotal role in inflammation and the immune response. The purpose of this study was to investigate the effects of UFMylation on lipopolysaccharide (LPS)-induced inflammatory responses in immortalized goat endometrial epithelial cells (gEECs). Ubiquitin-fold modifier conjugating enzyme 1 (UFM1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Interestingly, overexpression of UFL1 could alleviate ER stress and reduce cisplatin-induced damage to the ovary, in the end augmenting follicle number and restoring estrogen secreted by GCs to some extent. Similarly, UFM1 silencing was found to enhance ER stress but not oxidative stress-induced GC apoptosis during goat follicular development and atresia, suggesting a conserved role of UFMylation in the prevention of cell death related to the ER in ovaries ( 97 ).…”
Section: Ufmylation In Endocrine Glandsmentioning
confidence: 90%
“…Interestingly, overexpression of UFL1 could alleviate ER stress and reduce cisplatin-induced damage to the ovary, in the end augmenting follicle number and restoring estrogen secreted by GCs to some extent. Similarly, UFM1 silencing was found to enhance ER stress but not oxidative stress-induced GC apoptosis during goat follicular development and atresia, suggesting a conserved role of UFMylation in the prevention of cell death related to the ER in ovaries ( 97 ).…”
Section: Ufmylation In Endocrine Glandsmentioning
confidence: 90%
“…In domestic animals, ISG15 has been shown to be expressed in epithelial and stromal cells of the endometrium in cattle, horses, and sheep [ 32 , 33 , 34 ] and is located in the nucleus, nuclear stroma, cytoplasm, and organelles of bovine subcellular structures [ 32 ]. In the present study, LPS was used to induce an inflammatory response in gEECs to successfully construct an in vitro model of goat endometritis, as has been previously reported in earlier studies [ 26 ]. Here, we found that ISG15 was mostly localized in the cytoplasm, with low levels of expression in the nucleus, essentially consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the culture, the cells were collected for mRNA and protein experiments. The concentration of LPS was determined by previous studies in our laboratory and has been proved to cause an obvious inflammatory response of gEECs [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently researches have confirmed that UFL1 plays a crucial role in some biological process such as cell proliferation, differentiation and embryonic development (25)(26)(27)(28), but the function of UFL1 in POF has not been explored. In this study, we firstly revealed that UFL1 is expressed in GCs, oocytes and stromal cells in ovarian tissues.…”
Section: Discussionmentioning
confidence: 99%